Purchasing Power: Consumer Organizing, Gender, and the Seattle Labor Movement, 1919-1929 - Bergquist, Charles (Labour / Le Travail, 1995)
The article reviews the book, "Purchasing Power: Consumer Organizing, Gender, and the Seattle Labor Movement, 1919-1929," by Dana Frank.
Keywords: BOOKS – Reviews; FRANK; Dana; Nonfiction; PURCHASING Power: Consumer Organizing Gender & the Seattle Labor Movement 1919-1929 (Book); PURCHASING power